Light-dark regulation of carotenoid biosynthesis in pepper (Capsicum annuum)leaves - Simkin, A.J.; Zhu, C.; Kuntz, M.; Sandmann, G.
The carotenoid content in photosynthetic plant tissue reflects a steady state value resulting from permanent biosynthesis and concurrent photo-oxidation. The contributions of both reactions were determined in illuminated pepper leaves. The amount of carotenoids provided by biosynthesis were quantified by the accumulation of the colourless carotenoid phytoene in the presence of the inhibitor norflurazon. When applied, substantial amounts of this rather photo-stable intermediate were formed in the light. However, carotenoid biosynthesis was completely stalled in darkness. This switch off in the absence of light is related to the presence of very low messenger levels of the phytoene synthase gene, psy and the phytoene desaturase gene, pds. Other carotenogenic genes, such as zds, ptox and lcy-b also were shown to be down-regulated to some extent. By comparison of the carotenoid concentration before and after transfer of plants to increasing light intensities and accounting for the contribution of biosynthesis, the rate of photo-oxidation was estimated for pepper leaves. It could be demonstrated that light-independent degradation or conversion of carotenoids e.g. to abscisic acid is a minor process.
Keywords: CAROTENOID BIOSYNTHESIS; LIGHT REGULATION; PHOTODEGRADATION; PHYTOENE DESATURASE MESSENGER; PHYTOENE SYNTHASE MESSENGER